Environmental Quality, Institutions, and Financial Stability as Drivers of Well-being in Sub-Saharan Africa - Abdul Rahman, Mohammed Muntaka; Khan, Asad Ul Islam; Kaplan, Muhittin (International Journal of Energy Economics and Policy, 2025)
Sub-Saharan African (SSA) countries are among the countries with the lowest well-being and quality of life. Furthermore, SSA is characterized with weak institutions and financial systems, which makes it difficult for the realization of better quality of life and improve general well-being. This study examines the relationship between institutional quality, financial stability, and well-being. It further explores the role of poverty, food security, and environmental quality in this relationship. The study uses panel data of 26 SSA countries from 2011 to 2021 and employs the fully modified ordinary least squares and the dynamic ordinary least squares estimation techniques. The study finds that institutional quality, financial stability, food security, and environmental quality significantly enhance well-being. However, poverty and inflation negatively affect well-being by limiting access to essential resources and hindering economic and social progress. GDP per capita was found to be insignificant. The findings emphasize that well-being is not solely determined by economic growth but by broader social, environmental, and economic factors. It is suggested that SSA countries should implement policies that enhance institutional capacity, improve financial systems, ensure quality environment, and address poverty and food insecurity to improve the quality of life.